Climate Change Threatens the Geographic Distribution of Cupuaçu More Than Cacao: Insights from Ecological Modeling in Brazil - Leal Magalhães, Lean; Souza Tomaz, Jennifer; de Souza Bezerra, Caroline; Gomes Lopes, Maria Teresa; Lopes, Ricardo; Freitas de Souza, Samuel; Salvino Gadelha Meneses, Carlos Henrique; Virginia de Aguiar, Ananda; Vieira Capucho, Helinara Lais; Ferreyra Ramos, Santiago Linorio (Ethnobiology and Conservation, 2025)
The perpetuation and evolution of vegetal species can be impacted by climatic changes, and the projection of edaphoclimatic adaptation areas can be studied through ecological modeling. This study aimed to predict the distribution of Theobroma cacao L. (the cacao tree) and Theobroma grandiflorum (Willd. ex Spreng.) K. Schum (the cupuaçu tree) under current and future scenarios to identify areas suitable for environmental adaptation, conservation, and sustainable use. Ecological niche modeling was applied using 33 environmental variables. Results indicated that the cupuaçu tree is more vulnerable to climatic variations, with projections showing a relevant reduction in suitable areas in the Cerrado and Amazon. In contrast, the cacao tree demonstrated greater resilience, with potential expansion into areas such as the Pampa and Atlantic Forest. The modeling confirmed that climatic changes will negatively impact both species, with the cupuaçu tree facing higher susceptibility to loss of suitable areas, while the cacao tree may expand into new territories with appropriate environmental conditions. The study underscores the need for conservation efforts and sustainable use to contribute to the perpetuation of species, drawing from the wisdom of Indigenous peoples.